2017
DOI: 10.1039/c7nr00890b
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the pulmonary surfactant monolayer by single-walled carbon nanotubes: a molecular dynamics study

Abstract: Single-walled carbon nanotubes (SWCNTs) are at present synthesized on a large scale with a variety of applications. The increasing likelihood of exposure to SWCNTs, however, puts human health at a high risk. As the front line of the innate host defense system, the pulmonary surfactant monolayer (PSM) at the air-water interface of the lungs interacts with the inhaled SWCNTs, which in turn inevitably perturb the ultrastructure of the PSM and affect its biophysical functions. Here, using molecular dynamics simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…The analogous trend was found for NH particles at similar concentration, although these particles have much lower values of SSA and AR (≈ 400 m 2 /g, and ≤ 25, respectively). The observed effects may be caused by adsorption of LS molecules to the nanoparticles resulting in surfactant depletion, both on the interface and in the aqueous phase 22,41,42 . It should be noted though that the reported SSA values (Table 2) may be not equal to the area accessible for the adsorption of LS molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The analogous trend was found for NH particles at similar concentration, although these particles have much lower values of SSA and AR (≈ 400 m 2 /g, and ≤ 25, respectively). The observed effects may be caused by adsorption of LS molecules to the nanoparticles resulting in surfactant depletion, both on the interface and in the aqueous phase 22,41,42 . It should be noted though that the reported SSA values (Table 2) may be not equal to the area accessible for the adsorption of LS molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been shown that modeling lipid systems is a particular strength of the Martini model, see e.g. Refs 46,6062 . Another related question is how good is the Martini model for describing fullerene aggregation?…”
Section: Methodsmentioning
confidence: 99%
“…In vitro experiments show that the size and concentration of carbon nanotubes significantly change the mechanical response of the surfactant monolayer (Valle et al, 2015; Melbourne et al, 2015). Recent coarse-grained molecular dynamics simulations suggest that ultrashort SWCNTs (less than 5.5 nm) can insert into the surfactant monolayer via self-rotation (Yue et al, 2017), where the interaction morphology is determined by the length and diameter of SWCNTs and membrane tension of the surfactant (Xu et al, 2017). However, the detailed interaction between carbon nanotubes and lipid molecules could not be fully captured by coarse grained molecular dynamics simulations, and the energetics and molecular behaviors of lipids when carbon nanotubes translocate through the surfactant monolayer remain elusive.…”
Section: Testing Strategies For High Aspect Ratio Nanomaterials (Hmentioning
confidence: 99%